Health-related quality of life in patients with multiple sclerosis - Lázaro Aurelio Vázquez Gómez; Carlos Hidalgo Mesa; Benita Mabel Beltrán González; Yunier Broche Pérez; Ana María Mederos Herrera (Medisur)
Background: multiple sclerosis is a disease characterized by outbreaks of disability in any functional system that are produced by inflammation and demyelination of the central nervous system. Objective: to determine the health-related quality of life in patients with multiple sclerosis. Methods: a quasi-experimental, prospective longitudinal study with all patients diagnosed with multiple sclerosis with follow-up in Villa Clara during the period from 2017 to 2019. The study population consisted of 86 patients who were part of a multidisciplinary follow-up strategy. Results: regarding the modifications of the mental and physical component of the health state, it was observed that the mean score was 30.4 ± 9.7 and 39.9 ± 10.2 respectively before the strategy and 38.8 ± 9.3 and 51.5 ± 9.3 later respectively; so they moved to higher levels. On the visual impairment impact scale, the mean was 10.8 ± 2.2 before and 7.1 ± 2.8 after. Regarding the modifications in the mental health inventory, it was 58.1 ± 14.8 before and 47.2 ± 15.1 after. There was improvement in the impact of fatigue; pain effect; sexual satisfaction; bladder control; bowel control; impact of visual impairment; perceived cognitive deficit; mental health and social support. Conclusions: satisfactory modifications were achieved in the perceived quality of life scale, in the mental and physical health components, for which there was an improvement in health-related quality of life.